7z+2z=8z+3z

Simple and best practice solution for 7z+2z=8z+3z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7z+2z=8z+3z equation:


Simplifying
7z + 2z = 8z + 3z

Combine like terms: 7z + 2z = 9z
9z = 8z + 3z

Combine like terms: 8z + 3z = 11z
9z = 11z

Solving
9z = 11z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-11z' to each side of the equation.
9z + -11z = 11z + -11z

Combine like terms: 9z + -11z = -2z
-2z = 11z + -11z

Combine like terms: 11z + -11z = 0
-2z = 0

Divide each side by '-2'.
z = 0

Simplifying
z = 0

See similar equations:

| https://lh3.googleusercontent.com/0cuxbxkl1hi6FVa84GxswvxZa6JAPCHaTmuSPIDuZXiwn6gZ9tQIU-fH2wpMFP8dmMdmEZTK-w=w199 | | 250+130x=125+155 | | 5u-15+u+37=8u | | 8x-9=-5(x+2)+1 | | 5.8x+10-7.8x=8 | | 4(-2n+9)= | | 12x^2+3x=3 | | 6=w+4 | | v+v+2=v+48 | | x+20+x+20=x+50 | | 4log(4x)+3=11 | | 0.3x+0.7=-0.2 | | 9(-7+7n)= | | 2x+137=7x-8 | | 5(4x-6)+3=33 | | x-47+x=x+38 | | 15+2y-1=10y-14-4y | | -0.625x+14=-16 | | a+2b-c=equation | | 7(x+9)=5(x+2) | | -8(m+3)= | | 13x+4=-3x+20 | | -5(7h+5)+16=-6h-9+3h | | z-47+z-42=z+21 | | 2x^6-12x^4=0 | | 259=80-x | | 10(3+10k)= | | 9x+6=6x+(-6) | | 7t-7-4=5t-8 | | 3x=3y+6w | | 5+4=20091 | | 7x+12x+15x+3+16x+7=360 |

Equations solver categories